Gamma-spectrometer for measurement characteristics of radionuclides - Torgovkin, A.V.; Shramenko, B.I. (Вопросы атомной науки и техники, 2002)
Describing and metrological characteristics of spectrometric stand intend for measurement characteristics of radionuclides and its identification are present. The results of measurements specific activity of any radionuclides using this spectrometer are present too.